Patriachy and Ubuntu philosphy : the views of community elders in the Eastern Cape province - Luvalo, Loyiso Mennon (Penerbit Universiti Kebangsaan Malaysia, 2019)
South Africa still shows signs of being a very patriarchal society and this somehow leads to instances where the rights of women and children have been trampled on because of a male-favouring environment. This situation prevails despite the South African Constitution and current laws that prohibit discrimination based on gender. This study will explore whether the adoption of the philosophy of Ubuntu could offer a remedy for our society today, to counter the patriarchal views that dominate society and the ignorance these views reveal about both women and children’s rights. This paper draws on the study undertaken by the Eastern Cape chapter of South Africa’s National Research Foundation (NRF), namely “Archaeology of Ubuntu”, which explored the notion of Ubuntu as a moral concept. In the study, “Archaeology of Ubuntu”, the point of departure was that community elders, as the custodians of African epistemologies, should be consulted while still alive, because, once they are gone, all their wisdom and knowledge about the culture would be lost. In this paper, it is argued that the values propagated by the Ubuntu philosophy, and as it was practised in patriarchal societies the olden days, meant that the rights of women and children were not ignored. In this study, isiXhosa-speaking elders revealed that, based on the philosophy of Ubuntu, patriarchy enabled a caring society, where the vulnerable, that is, women, children and the elderly, were looked after, protected and provided for. Therefore, the conclusion is that the Ubuntu philosophy should be considered to address patriarchy in South African society, to remedy the ever-increasing incidents of abuse of women and children.